PENDAFTARAN TANAH DI EROPA DAN ASIA: STUDI KOMPARASI KEBIJAKAN DAN DAMPAK KEPASTIAN HUKUM - Ruth Elita Gultom; Chelsy Naristya; Adymas Hikal; Aprilia Niravita (JURNAL ILMIAH NUSANTARA, 2024)
This article aims to analyze and compare land registration policies in Europe and Asia and their impact on legal certainty in both regions. The study employs a comparative method, using literature review and policy analysis focused on differences in administrative structures, technology, and community involvement in land registration systems. The main findings reveal that land registration systems in Europe, typically centralized and registry-based, provide a higher degree of legal certainty than many Asian countries, where decentralized approaches and manual methods are often used. These variations influence public trust, investment climate, and legal stability in each region. In conclusion, this study highlights the importance of technology integration and policy standardization to enhance legal certainty, particularly in Asia.